Differential Regulation of Type I and Type III Interferon Signaling - Stanifer, Megan L. (Int J Mol Sci, 2019)
Interferons (IFNs) are very powerful cytokines, which play a key role in combatting pathogen infections by controlling inflammation and immune response by directly inducing anti-pathogen molecular countermeasures. There are three classes of IFNs: type I, type II and type III. While type II IFN is specific for immune cells, type I and III IFNs are expressed by both immune and tissue specific cells. Unlike type I IFNs, type III IFNs have a unique tropism where their signaling and functions are mostly restricted to epithelial cells. As such, this class of IFN has recently emerged as a key player in mucosal immunity. Since the discovery of type III IFNs, the last 15 years of research in the IFN field has focused on understanding whether the induction, the signaling and the function of these powerful cytokines are regulated differently compared to type I IFN-mediated immune response. This review will cover the current state of the knowledge of the similarities and differences in the signaling pathways emanating from type I and type III IFN stimulation.